Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.